Student’s scientific literacy on environmental pollution material based on SETS learning approach combined with Vee Diagram - Rini Rita T. Marpaung; Berti Yolida; Faradilla Riana Putri (University of Muhammadiyah Malang, 2021)
The student’s scientific literacy is vital in improving students’ awareness of several issues. This study was intended to describe the effect of the SETS learning approach combined with Vee Diagram on students’ scientific literacy especially on Environmental Pollution Material. This study used a nonequivalent pretest-posttest control group design. The survey involved 60 students who were selected using cluster random sampling technique. The quantitative data, in terms of pretest, posttest, and N-gain scores were analyzed using Independent-sample t-test at the 5% significance level. The results showed that, based in the N-gain scores, the experiment class was classified in moderate category and the control class belonged to low category. This means that the SETS learning approach combined with Vee Diagram influence student’s scientific literacy on Environmental Pollution Material. Therefore, this combination is recommended to be implemented in class to enhance students' scientific literacy skills.